Notice: Payments for answers will end 4/10/2017. Click for more info.
You have new items in your feed. Click to view.
Question and answer
Q: -3/7x=6/35
A: -3/7x = 6/35 x = (6/35) / (-3/7) x = (6/35) * (-7/3) x = (6 * -7) / (35 * 3) x = -42/105 x = -2/5
Get an answer
Original conversation
User: -3/7x=6/35

Weegy: 3/7x= 12/35, x=12/35*7/3, x=84/105
debnjerry|Points 27527|

Question
Asked 3/1/2012 5:03:41 PM
Updated 6/3/2014 3:42:38 PM
1 Answer/Comment
This conversation has been flagged as incorrect.
Flagged by alfred123 [6/3/2014 3:42:38 PM]
New answers
Rating
3
-3/7x = 6/35

x = (6/35) / (-3/7)

x = (6/35) * (-7/3)

x = (6 * -7) / (35 * 3)

x = -42/105

x = -2/5
Added 6/3/2014 3:42:36 PM
This answer has been confirmed as correct and helpful.
Confirmed by andrewpallarca [6/3/2014 3:52:56 PM]
Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
n=m+v for m
Weegy: Can you please elaborate your question ? (More)
Question
Expert Answered
Updated 5/10/2014 6:44:27 PM
2 Answers/Comments
In n = m + v, m = n - v.
Added 3/1/2012 6:32:26 PM
This answer has been confirmed as correct and helpful.
Confirmed by andrewpallarca [5/10/2014 6:44:28 PM]
4y + 16 = 20
Question
Expert Answered
Updated 196 days ago|12/3/2017 1:32:26 AM
1 Answer/Comment
4y + 16 = 20
4y = 20 - 16
4y = 4
y = 4/4
y = 1
Added 196 days ago|12/3/2017 1:32:26 AM
This answer has been confirmed as correct and helpful.
2*4(p-4)+15-2(55-3)+2
Question
Not Answered
Updated 113 days ago|2/24/2018 6:37:16 AM
1 Answer/Comment
2*4(p-4)+15-2(55-3)+2 =8p-32+15-110+ 6+2 = 8p -119
Added 113 days ago|2/24/2018 6:37:16 AM
This answer has been confirmed as correct and helpful.
Confirmed by jeifunk [2/24/2018 10:11:41 AM]
4(x+4)=6(x-2)
Question
Not Answered
Updated 1/1/2017 6:16:35 PM
1 Answer/Comment
4(x + 4) = 6(x - 2)
4x + 16 = 6x - 12
4x - 6x = -12 - 16
2x = -28
x = -28/2
x = -14
Added 1/1/2017 6:16:35 PM
This answer has been confirmed as correct and helpful.
solve for y if 4y-8+y=6y+40-4y
Question
Not Answered
Updated 5/10/2014 6:41:17 PM
1 Answer/Comment
4y-8+y=6y+40-4y;

5y - 8 = 2y + 40;

5y - 2y = 40 + 8;

3y = 48;

y = 48/3;

y = 16
Added 5/10/2014 6:41:17 PM
This answer has been confirmed as correct and helpful.
26,991,432 questions answered
*
Get answers from Weegy and a team of really smart lives experts.
S
L
Points 226 [Total 244] Ratings 0 Comments 156 Invitations 7 Offline
S
L
Points 130 [Total 130] Ratings 0 Comments 130 Invitations 0 Offline
S
L
R
Points 105 [Total 256] Ratings 1 Comments 5 Invitations 9 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 59 [Total 13326] Ratings 0 Comments 59 Invitations 0 Offline
S
L
1
R
Points 31 [Total 1447] Ratings 2 Comments 11 Invitations 0 Offline
S
Points 20 [Total 20] Ratings 1 Comments 0 Invitations 1 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.